Pemanenan Air Hujan Pada Wilayah Kepulauan Sebagai Upaya Peningkatan Akses Air Bersih Di Sekolah Tanjungpinang - Gunnara, Harvensica; Daswito, Rinaldi (Poltekes Kemenkes Tanjungpinang, 2025)
The community's clean water needs in Tanjungpinang are managed by the Tirta Kepri Regional Water Utility (PDAM). According to data from the Central Statistics Agency (BPS) of Tanjungpinang City in 2020, the population reached 227,663 people, resulting in an estimated clean water requirement of 22,766,300 liters per day (based on 100 liters per person per day for medium-classified cities). However, clean water production in 2020 only met 17.5 liters per person per day. The limited availability of clean water sources in schools has become a major obstacle in promoting Clean and Healthy Living Behavior (PHBS), as schools rely solely on PDAM supply and one well, which does not meet quality standards. The Rainwater Harvesting System (PAH) presents an alternative solution, considering Tanjungpinang's high and evenly distributed rainfall throughout the year. This activity aims to improve access to clean water in schools through the installation of PAH devices and educational outreach to teachers and students. Partners contributed in providing equipment and materials, as well as supporting sustainability evaluations, while schools were responsible for installation and maintenance of the devices. The results show that PAH devices have been effectively used as a source of clean water in the school’s prayer room (mushala) and that teachers and students have mastered their maintenance. This program has resulted in a mandatory output in the form of an activity report and an additional output in the form of intellectual property rights (IPR) for the PAH Pocket Book in support of Adiwiyata Schools.